Diamond nanoparticles-porphyrin mthpp conjugate as photosensitizing platform: Cytotoxicity and antibacterial activity - Hurtado, Carolina Ramos; Hurtado, Gabriela Ramos [UNESP]; de Cena, Gabrielle Lupeti; Queiroz, Rafaela Campos; Silva, Alexandre Vieira; Diniz, Milton Faria; Dos Santos, Verônica Ribeiro; Trava-Airoldi, Vladimir; Baptista, Maurício da Silva; Tsolekile, Ncediwe; Oluwafemi, Oluwatobi Samuel; Conceição, Katia; et al. (MDPI, 2021)
Conjugation of photosensitizers (PS) with nanoparticles has been largely used as a strategy to stabilize PS in the biological medium resulting in photosensitizing nanoparticles of enhanced photoactivity. Herein, (Meso-5, 10, 15, 20-tetrakis (3-hydroxyphenyl) phorphyryn (mTHPP) was conjugated with diamond nanoparticles (ND) by covalent bond. Nanoconjugate ND-mTHPP showed suitable stability in aqueous suspension with 58 nm of hydrodynamic diameter and Zeta potential of −23 mV. The antibacterial activity of ND-mTHPP was evaluated against Escherichia coli for different incubation times (0–24 h). The optimal activity was observed after 2 h of incubation and irradiation (660 nm; 51 J/cm2 ) performed right after the addition of ND-mTHPP (100 µg/mL) to the bacterial suspension. The inhibitory activity was 56% whereas ampicillin at the same conditions provided only 14% of bacterial growth inhibition. SEM images showed agglomerate of ND-mTHPP adsorbed on the bacterial cell wall, suggesting that the antimicrobial activity of ND-mTHPP was afforded by inducing membrane damage. Cytotoxicity against murine embryonic fibroblast cells (MEF) was also evaluated and ND-mTHPP was shown to be noncytotoxic since viability of cells cultured for 24 h in the presence of the nanoconjugate (100 µg/mL) was 78%. Considering the enhanced antibacterial activity and the absence of cytotoxic effect, it is possible to consider the ND-mTHPP nanoconjugate as promising platform for application in antimicrobial photodynamic therapy (aPDT).
Keywords: Drug-resistance; Nanoconjugate; Photodynamic antimicrobial therapy (aPDT); Photosensitizers (PS)